2018
DOI: 10.1186/s13046-018-0805-4
|View full text |Cite|
|
Sign up to set email alerts
|

3-O-acetyl-11-keto-β-boswellic acid exerts anti-tumor effects in glioblastoma by arresting cell cycle at G2/M phase

Abstract: BackgroundGlioblastoma (GBM) is the most common, malignant, and lethal primary brain tumor in adults accounting for about 50% of all gliomas. Up to now, the chemotherapy approaches for GBM were limited. 3-O-acetyl-11-keto-β-boswellic acid (AKBA), the major active ingredient of the gum resin from Boswellia serrata and Boswellia carteri Birdw., was reported to inhibit the growth of many types of cancer cells; however, the underlying mechanism of its anticancer effects are still unclear.MethodsThe effects of AKBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 57 publications
(54 reference statements)
2
36
0
3
Order By: Relevance
“…10,11 Recently, AKBA was also found to exhibit antitumor effects in human cell lines established from prostate cancer, breast cancer and glioblastoma. [12][13][14] Csuk et al demonstrated that boswellic acid and its derivatives induce apoptosis in breast and cervical cancers cells. 15 Liu indicated that AKBA inhibits the proliferation and cancer stem cell-like properties of docetaxel resistant prostate cancer cells in vitro and in vivo via blocking Akt and Stat3 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recently, AKBA was also found to exhibit antitumor effects in human cell lines established from prostate cancer, breast cancer and glioblastoma. [12][13][14] Csuk et al demonstrated that boswellic acid and its derivatives induce apoptosis in breast and cervical cancers cells. 15 Liu indicated that AKBA inhibits the proliferation and cancer stem cell-like properties of docetaxel resistant prostate cancer cells in vitro and in vivo via blocking Akt and Stat3 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…For the compounds 5 a‐5 o anticancer activity were preliminarily evaluated against Hepatocellular carcinoma (HepG2), Epidermoid Carcinoma‐2 (HEp‐2) and breast cancer (MCF‐7) cell lines in vitro by using standard 2‐(2‐ methoxyl‐4‐nitrophenyl)‐3‐(4‐nitrophenyl)‐5‐(2,4‐disulfonyl‐benzene)‐2H‐tetrazolium monosodium salt (CCK8) assay after exposure of cells to the tested compounds for 48 h (with gefitinib and cisplatin as the reference drug against HEp‐2 cell lines) ,. The results expressed as halfmaximal inhibitory concentration (IC 50 ) values, are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Die g2/m-Phase des Zellzyklus ist gekennzeichnet durch die Zweiteilung des Zellkerns (Mitose). Eine Arretierung des Zellzyklus in der G2/M-Phase wurde an Gliomazellen durch AKBA [24] über verschiedene Wege beobachtet und zwar über eine "Downregulation" des Aurora B/TOP2A-sowie über die Regulation des p21/ FOXM1/Cyclin B1-Signalweges.…”
Section: Wirkungen Auf Verschiedene Tumorzelllinienunclassified
“…Untersucht wurde deren Wirkung auf die Caspasen 1, 3, 8, 9. Wie zu erwarten war, fand sich bei AKBA eine Aktivierung der Apoptose bei Hep G2-Zellen [29] und Glioblastomzellen [24]. Eine Aktivierung der Caspasen 3, 8, 9 und damit der Apoptose bei Hep G2-Zellen wurde auch bei Verwendung von KBA festgestellt [29].…”
Section: Signalwege Der Apoptoseunclassified